Management of Royalties on Songs and/or Music in Indonesia - Sunputri, Margareta Fanandi; Handono, Mardi; Sari, Nuzulia Kumala (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2025)
The existence of a royalty system is a form of protection and fulfillment of economic rights for creators, copyright holders and owners of related rights to songs and/or music. In order to carry out royalty management for songs and/or music in Indonesia, a Collective Management Institution (which is referred to as LMK) and a National Collective Management Institution (which is referred to as LMKN) were formed. LMK and LMKN in this case have the authority to attract, collect, and distribute royalties. Through this article, the author wants to explain the management of royalties on songs and/or music in Indonesia, related to institutions authorized to carry out royalty management on songs and/or music in Indonesia, the implementation of royalty management on songs and/or music, as well as the settlement efforts that can be taken if there is a dispute over royalty management on songs and/or music in Indonesia. This research is a normative juridical research type, using the Legislation Approach and Conceptual Approach. Through this research, it can be concluded that LMK and LMKN are both entitled to carry out royalty management of songs and/or music in Indonesia. Where the withdrawal of royalties is carried out by LMKN, while the collection and distribution are carried out by LMK and LMKN. Regarding dispute resolution efforts, if there is a dispute regarding the distribution of royalties, the resolution is mediation through LMKN, while for royalty withdrawal disputes can be resolved in accordance with the provisions contained in the Copyright Law.